Study of multivesiculated polyester particles synthesis by double emulsion process - Ângela Dias (2013)
This work studies the synthesis of multivesiculated particles (MVPs) from a w/o/w double emulsion comprising water and unsaturated polyester dissolved in styrene. These particles can be used as opacifying agents in paint formulations, due to light refraction within the air-containing voids, after water evaporation. The effect of some key variables was analyzed: time of dispersion and concentrations of added amine, polyester and protective colloids. The final products were characterized in terms of particle size distribution, vesicle morphology and dry film opacity. All the studied variables were shown to play a role in the quality of vesiculation. The underlying mechanisms were proposed, allowing for a better understanding of this sparsely studied process.